2006
DOI: 10.1088/0964-1726/15/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of power output for piezoelectric energy harvesting systems

Abstract: Power harvesting refers to the practice of acquiring energy from the environment which would be otherwise wasted and converting it into usable electric energy. Much work has been done on studying the optimal AC power output, while little has considered the AC-DC output. This article investigates the optimal AC-DC power generation for a rectified piezoelectric device. In contrast with estimates based on various degrees of approximation in the recent literature, an analytic expression for the AC-DC power output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
589
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 675 publications
(604 citation statements)
references
References 56 publications
11
589
1
3
Order By: Relevance
“…The consequence of pronounced shift in natural frequency from sc to oc leads to completely distinct optimization schemes for maximum power extraction. Shu and Lien [34] have studied the ac-dc power output for a rectified piezoelectricbased harvesting device. They have shown that the average harvested power has two identical peaks evaluated at two different electric loads at the respective operating points provided that k 2 e ζm 1 while it has only one peak otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of pronounced shift in natural frequency from sc to oc leads to completely distinct optimization schemes for maximum power extraction. Shu and Lien [34] have studied the ac-dc power output for a rectified piezoelectricbased harvesting device. They have shown that the average harvested power has two identical peaks evaluated at two different electric loads at the respective operating points provided that k 2 e ζm 1 while it has only one peak otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The vibrations energy harvesting principle using piezoelectric materials [4] is illustrated in figure 4. The conversion chain starts with a mechanical energy source: bike.…”
Section: Piezoelectric Generator Principlementioning
confidence: 99%
“…The measurement results are summarized in Table 3. The optimal load was found to be inversely proportional to the capacitance of the piezoelectric material [44,45]. For the same dimensions of the beam shape of the d31 and d33 mode devices, it was obvious that the capacitance of the d31 mode device was larger than the d33 mode device.…”
Section: Comparison Between D31 and D33 Mode Piezoelectric Mems Genermentioning
confidence: 99%